The morphologies of twins in tetragonal ferroelectrics - Ningbo He; Cuiping Li; Chihou Lei; Yunya Liu (Frontiers in Materials, 2022)
Twins, as a special structure, have been observed in a small number of experiments on ferroelectrics. A good understanding of the morphologies of twins is very important for twin engineering applications in ferroelectric materials. In this work, the morphologies of twins in tetragonal ferroelectrics are investigated using the compatibility analysis of the transformation strains and spontaneous polarization and the energetic analysis. The tetragonal BaTiO3 single crystal is chosen as an example for the material system. The results show that the lamellar twin structures with 111 as the twin plane have been identified by both compatibility analysis and energetic analysis, which is consistent with the experimental observations. In addition to 111 twin structures, 12¯1 and 21¯5 twin structures can also appear in tetragonal ferroelectrics. Furthermore, stable state uncharged twin boundaries and metastable charged twin boundaries are distinguished by energetic analysis, where the spontaneous polarization is compatible across the uncharged twin boundaries, while it is not compatible across the charged twin boundaries. The results predicted by the compatibility analysis and energetic analysis are consistent, thus providing a pathway for understanding the morphologies of twins.